Acacia Senegal (Gum Arabic) Supplementation Modulate Lipid Profile and Ameliorated Dyslipidemia among Sickle Cell Anemia Patients. (18th June 2019) - Kaddam, Lamis; Fadl-Elmula, Imad; Eisawi, Omer Ali; Abdelrazig, Haydar Awad; Saeed, Amal M.
Abstract : Background . Sickle cell disease (SCD) is an inherited haemolytic anemia with a variable course and severity. Knowledge of prognostic biomarkers may help in the establishment of therapeutic intervention, management, and follow-up of patients. There have been scattered reports of low high-density lipoprotein cholesterol (HDL-C) and increased triglyceride (TG) in SCD patients. In addition, TG levels have been suggested to be elevated in patients with increased endothelial activation. An increased TG level has been associated with haemolysis, vascular dysfunction, and increased prevalence of pulmonary hypertension. Gum Arabic (GA) is an edible, dried, gummy exudate from the acacia Senegal tree. Several studies on GA ingestion have shown reduced plasma cholesterol and low-density lipoprotein (LDL) concentrations in both animals and humans. We investigated GA's therapeutic potential to modulate serum lipids in patients with sickle cell anemia. Methods . This study recruited and documented secondary outcomes in 47 patients (aged 5–42 years) carrying hemoglobin SS. The patients received 30 g/day of GA for 12 weeks. Total cholesterol, TG, LDL, and HDL were measured before and after GA intake. Cobas C311 (Roche, Germany) automated chemistry analyser was used for direct determination of the values of the lipid profile. Results . GA significantly decreased total cholesterol (TC), TG, and LDL ( p = 0.006, 0.04, and 0.02, resp.). GA showed no effect on HDL level. Baseline serum TG and LDL correlated significantly with the hydrogen peroxide (H2 O2 ) level, which is known as an oxidative stress marker ( p = 0.003 and 0.04, resp.). None of the lipid profile elements correlated with age. Conclusion . Our results revealed that dyslipidemia in sickle cell patients is associated with oxidative stress but not associated with age. The findings showed that GA significantly decreased TC, LDL, and TG levels, revealing a novel effect of GA, which is considered a natural dietary fibre that can modulate lipid profile in patients with sickle cell anemia. Trial Registration . This retrospective trial is registered with ClinicalTrials.gov Identifier:NCT02467257 on 3 June, 2015.